The schools of the prophets - Quinteros Del Águila, Francisco (2013)
The author explores the relationship between current education and schools of the prophets as an educational model. This is part of a historical study to identify the schools of the prophets in the Bible and in the writings of Ellen White. This paper proposes a reflection on christian education from a biblical platform, whichprovides for a spirit of deep christian devotion and the teachers, the relationship of the study and work as a distinctive feature of the student as well as personalized tutorial attention, which is equivalent to an educational model that well would force teachers and administrators to imitate.